Instilling environmentally responsible behavior (erb) in adolescents in Akinyele Local Government area of Oyo State, Nigeria (2021)
Globally, environmental issues and challenges have been on for ages and are sprouting on a daily basis. This is evident in environmental disturbances which are caused by pollution (air, water and land), floods, litters, poor housing conditions, overcrowding, poor planning and ventilation, uncontrolled waste disposal dumping, unapproved industry set-ups, poorly structured cattle market and abattoirs. These have affected human, plant, animals and natural resources to a large extent. Residents and non-dwellers working in Akinyele Local Government Area of Oyo state are not exempted from this. The findings show that the adolescents are not equipped with enough environmental knowledge, skills and values which are capable of promoting required environmental behavior in them. Due to its urbanizing nature, there has been untoward hardship arising from lack of basic infrastructural facilities, open sewers, polluted environment. There is high level of unhealthy living conditions and hazardous locations as people living within the axis are facing filthy and unsafe environment. The study recommends instilling environmentally responsible behavior and values in young ones so to ameliorate the evil effects of non-challant attitude to the environment.